Serious Human Rights Crimes - Chifa Azyana Adly meknesya; Muhammad Rafly Lubis; Meldyana Permata Abdillah; Muhammad Faiz Almaisi (ISNU Sumatera Utara, 2026)
Gross human rights crimes are serious violations of basic human rights that receive attention in both national and international law. This paper aims to examine the concept and scope of gross human rights crimes, their regulation in Indonesian national law, and the position of war crimes from the perspective of international criminal law. The research method used is normative legal research with a statutory and conceptual approach, through a literature review of primary and secondary legal materials. The results of the discussion indicate that Indonesian national law, through Law Number 26 of 2000 concerning Human Rights Courts, regulates gross human rights violations in a limited manner, namely genocide and crimes against humanity. Meanwhile, in international criminal law, war crimes are recognized as international crimes that occur in the context of armed conflict and are closely related to the protection of human rights. Thus, the study of gross human rights crimes and war crimes demonstrates the relationship between national law and international law in efforts to protect human dignity